2021
DOI: 10.3390/ejihpe12010002
|View full text |Cite|
|
Sign up to set email alerts
|

Higher Order Thinking by Setting and Debriefing Tasks in Dutch Geography Lessons

Abstract: Tasks are a powerful instrument for geography teachers, as they let students engage with the subject. To advance the cumulative learning of students, teachers have to make sure that students learn how to deal with complex and abstract knowledge structures. In the Netherlands, teachers face a dilemma when it comes to task setting: the intended curriculum aims for a considerable part at (parts of) higher order thinking, whereas the high-stakes exams have a clear focus on the use of thinking strategies. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Şanlı and Sezer (2018) found that the content of the textbook is supportive of students' cognitive development. The international literature has suggested that the tasks in geography textbooks are mostly oriented to the middle and lower categories of cognitive taxonomies (Bijsterbosch, 2018;Jo & Bednarz, 2009;Krause et al, 2022a). It can thus be said that textbooks used in geography teaching generally encourage developing students' interpretation skills in the context of critical thinking skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Şanlı and Sezer (2018) found that the content of the textbook is supportive of students' cognitive development. The international literature has suggested that the tasks in geography textbooks are mostly oriented to the middle and lower categories of cognitive taxonomies (Bijsterbosch, 2018;Jo & Bednarz, 2009;Krause et al, 2022a). It can thus be said that textbooks used in geography teaching generally encourage developing students' interpretation skills in the context of critical thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers consider all forms of thinking other than remembering information to be higher-order thinking (Bijsterbosch, 2018;Maude & Caldis, 2019), while others accept only the "analysis", "evaluation" and "reconstruction" of information as higher-order thinking (Anderson, et al, 2001;Jo & Bednarz, 2009). Thus, the processes of abstraction such as "classification, understanding importance, and clarification", which are the components of the "interpretation" skill, should be accepted as the foundations of high-order thinking (Krause et al, 2022a;2022b). According to Bernstein (2000), the actions of classification and clarification always work together, and learning progresses from concrete information and simple procedures to the production of more abstract and complex knowledge structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original publication [ 1 ], there was a mistake in the Citation . For the author’s name “Jan van Tartwijk-, Tartwijk, J.v.…”
Section: Incorrect Last Name In Citationmentioning
confidence: 99%
“…In the original publication [ 1 ], there was a mistake in Figure 1 , as published. For “semantic gravity”, “strong” and “weak” should be reversed.…”
Section: Error In Figurementioning
confidence: 99%